Sustainable Crafting: Pelatihan Ecoprint pada Barang Pakai Sehari-hari sebagai Gerakan Peduli Lingkungan - Arshy Prodyanatasari,; Djembor Sugeng Walujo,; Anita Kusuma Wardani,; Bella Prima Herliana,; Adellia Putri Permata Sari,; Ananda Ika Trisnawati,; Dhiadjeng Waluyaning Ati,; Atika Yon Saputri,; Lisviana Putri, (Jurnal Pengabdian Masyarakat dan Penerapan Ilmu Pengetahuan, 2025)
This community service activity was motivated by the importance of developing sustainable practices in Wates Village, Kediri Regency, amid growing environmental awareness and the potential of local UMKM. Ecoprint, as an environmentally friendly technique, offers an innovative solution to create value-added products while reducing the negative impact of the conventional textile industry. The objectives of this activity are: (1) to enhance skills in creating ecoprint on everyday items, (2) to expand the variety of SME products, and (3) to develop a sustainable business model based on local potential. The implementation method uses a hands-on approach, including demonstrations of ecoprint techniques on mugs, tumblers, and goodie bags, product design guidance, and circular economy education with the creation of digital-based promotional materials. The activity was conducted on 16 August 2025 at the Wates Village SME Centre, Kediri Regency, attended by the Wates Village PKK (Family Welfare Movement) members. The activity outcomes included participants mastering ecoprint techniques on various media such as mugs, tumblers, and goodie bags, and creating market-ready products with innovative designs using local natural materials. This activity also strengthened collaboration between UMKM, the community, and KKN students for the development of sustainable creative economy. Recommendations include: (1) developing a sustainable ecoprint training centre in Wates Village, (2) integrating with the village tourism programme, and (3) expanding the digital marketing network. These activities prove thatecoprint-based empowerment can be a model for environmentally-friendly UMKM development in rural areas.